Heat Sepsis Precedes Heat Toxicity in the Pathophysiology of Heat Stroke-A New Paradigm on an Ancient Disease - Chin Leong Lim (MDPI AG, 2018)
Heat stroke (HS) is an ancient illness dating back more than 2000 years and continues to be a health threat and to cause fatality during physical exertion, especially in military personnel, fire-fighters, athletes, and outdoor laborers. The current paradigm in the pathophysiology and prevention of HS focuses predominantly on heat as the primary trigger and driver of HS, which has not changed significantly for centuries. However, pathological and clinical reports from HS victims and research evidence from animal and human studies support the notion that heat alone does not fully explain the pathophysiology of HS and that HS may also be triggered and driven by heat- and exercise-induced endotoxemia. Exposure to heat and exercise stresses independently promote the translocation of lipopolysaccharides (LPS) from gram-negative bacteria in the gut to blood in the circulatory system. Blood concentration of LPS can increase to a threshold that triggers the systemic inflammatory response, leading to the downstream ramifications of cellular and organ damage with sepsis as the end point i.e., heat sepsis. The dual pathway model (DPM) of HS proposed that HS is triggered by two independent pathways sequentially along the core temperature continuum of >40 °C. HS is triggered by heat sepsis at Tc < 42 °C and by the heat toxicity at Tc > 42 °C, where the direct effects of heat alone can cause cellular and organ damage. Therefore, heat sepsis precedes heat toxicity in the pathophysiology of HS.